Algae Polysaccharides’ Chemical Characterization and their Role in the Inflammatory Process - Florez, Noelia; Jesus Gonzalez-Munoz, Maria; Ribeiro, Daniela; Fernandes, Eduarda; Dominguez, Herminia; Freitas, Marisa (Current Medicinal Chemistry, 2017)
Polysaccharides are abundant components in marine macroalgae with potential applications in different areas such as pharmaceutical, biomedical, cosmetics and nutrition. The current interest in these compounds is due to their known bioactivities, conferred by their antiallergic, neuroprotective, gastroprotective, cardioprotective, cytotoxic, anticoagulant/antithrombotic, antiviral, antilipidemic, antinociceptive, and immunomodulatory properties, making them promising bioactive products and biomaterials. The inflammatory process is a complex event mediated by the immune system that culminates in the neutralization and elimination of the offending insult protecting the host and restoring tissue homeostasis. This review focuses on the extraction procedures and chemical characterization of polysaccharides from different classes of algae (Phaeophyceae, Rhodophyceae and Chlorophyceae) and on the studies on their inflammatory process modulatory effect.
Keywords: inflammation